ANALISIS FAKTOR YANG BERHUBUNGAN TERHADAP PERILAKU SADARI PADA REMAJA - L.Tobing, Hendri Parluhutan; Sulistiyowati, Sulistiyowati; Noora, Nilam; Harni, Harni; Afdhal, Muhammad Ridha (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Breast self-examination (SADARI) is a secondary prevention of breast cancer, but has not been effectively implemented in Jambi Province. This study aims at factors associated with SADARI behavior in adolescents. This research is a quantitative study with a cross sectional study design. The research was conducted at SMA Negeri 1 Jambi in December 2023. The study sample amounted to 63 people who were selected using proportional stratified random sampling. The research instrument used a research questionnaire. The analysis carried out was univariate and bivariate analysis. The results showed that there was a relationship between information exposure (p value: 0.000) to awareness behavior in adolescents and there was no relationship between knowledge and awareness behavior in adolescents. It is recommended for students to have awareness and interest in seeking information related to breast cancer prevention. This can be done by browsing social media pages that discuss health that can be found on; (Twitter and Instagram) or visiting the local health center. SADARI information can be obtained from family/mother, peers, social media and health care workers.Keywords: Information Exposure, Knowledge, SADARI